2021
DOI: 10.1002/mas.21720
|View full text |Cite
|
Sign up to set email alerts
|

Combined atomic and molecular (CAM) ionization with the liquid sampling‐atmospheric pressure glow discharge microplasma

Abstract: In a world where information‐rich methods of analysis are often sought over those with superior figures of merit, there is a constant search for ionization methods which can be applied across diverse analytical systems. The liquid sampling‐atmospheric pressure glow discharge (LS‐APGD) is a microplasma device which has the inherent capabilities to operate as a combined atomic and molecular (CAM) ionization source. The plasma is sustained by placement of a high voltage (~500 V, dc) onto an electrolytic solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 99 publications
0
9
0
Order By: Relevance
“…Characterization of Ionized Pu-Species and Utilization of Collisional Dissociation Modalities. While the CAM ionization capabilities of the microplasma are powerful in understanding solution phase chemistries, 23,29,41 the use of the LS-APGD in an elemental/isotopic mode requires that analyte-containing species be broken down to their simplest form to achieve high sensitivity and reduce influences of solution chemistry. Solvent-related species, both analyte and background, are frequently encountered with solution-based atmospheric pressure plasma sources.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Characterization of Ionized Pu-Species and Utilization of Collisional Dissociation Modalities. While the CAM ionization capabilities of the microplasma are powerful in understanding solution phase chemistries, 23,29,41 the use of the LS-APGD in an elemental/isotopic mode requires that analyte-containing species be broken down to their simplest form to achieve high sensitivity and reduce influences of solution chemistry. Solvent-related species, both analyte and background, are frequently encountered with solution-based atmospheric pressure plasma sources.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A dual-electrode LS-APGD ionization source was coupled to the Orbitrap mass spectrometer, as described previously , and presented diagrammatically in Figure . This source has demonstrated superior sensitivity over the single-electrode mode, as illustrated in Supporting Information (SI) Figure S1.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solvent selection provides the means of obtaining atomic/elemental and/or molecular mass spectra. Marcus et al 46 provided an overview of the varied modes of sample introduction and MS platforms to which the LS-AP-GD has been interfaced. Representative spectra and analytical figures of merit for elemental and IR measurements were presented, in addition to descriptions of the application to small organic molecules, organometallic complexes, and intact proteins.…”
Section: Liquids Analysismentioning
confidence: 99%
“…Finally, we had incidentally observed that the SAWN-APCI method demonstrated capability for small protein ionization under native conditions as similar techniques have previously. 28 In Figure 7A, we show the mass spectrum of sampled droplets containing 14 kDa cytochrome C and spiked DOPC lipid with formal concentrations of 12.5 and 25 μM, respectively, observed by SAWN-APCI alone. In Figure 7B, the cytochrome C is spiked into the DOPC liposome solution (not incorporated into the liposomes themselves), which is then subjected to 40 s of 64 MHz SAWs prior to SAWN-APCI.…”
Section: ■ Introductionmentioning
confidence: 99%